Evaluation of Norges Bank's Projections for 2011 - Einar W. Nordbø (Norges Bank, 2012)
Since the conduct of monetary policy relies on projections for economic developments, it is important to evaluate these projections. In this article, we assess Norges Bank's projections for economic developments in 2011. Mainland GDP growth in 2011 was lower than projected in the October 2010 Monetary Policy Report and subsequent Reports through 2011. Increasing uncertainty regarding the global economy from summer onward resulted in a marked shift in sentiment and was a likely factor in dampening activity growth in Norway. An average of projections from other forecasters and projections from the Bank's System for Averaging short-term Models (SAM) more closely predicted actual developments in 2011. CPI-ATE inflation was also somewhat lower than expected, though Norges Bank's projections were more accurate than an average of projections from other forecasters. We have also examined the short-term projections for output and inflation over time. In the past three years, CPI-ATE inflation and mainland GDP growth have been somewhat lower than expected. When we look at projections over a longer period, CPI-ATE inflation has been lower than forecast, while GDP growth on average has been approximately as assumed. While the short-term projections for GDP in the Monetary Policy Report have been more accurate than the projections derived from SAM, CPI-ATE projections have been approximately as accurate as the projections derived from SAM.
hdl:11250/2507188
Keywords: 330